Anti-Hu-associated brainstem encephalitis. Issue 4 (17th November 2008) - Saiz, A; Bruna, J; Stourac, P; Vigliani, M C; Giometto, B; Grisold, W; Honnorat, J; Psimaras, D; Voltz, R; Graus, F
Abstract : Objective: A series of patients with anti-Hu-associated brainstem encephalitis is reviewed to better define the clinical presentation and to improve its recognition. Methods: Data were collected from 14 patients diagnosed by members of the Paraneoplastic Neurological Syndromes Euronetwork, and eight patients from the literature who presented with isolated brainstem encephalitis and had anti-Hu antibodies. Results: The median age of the 22 patients was 64 years (range 42–83), and 50% were men. All patients developed a subacute neurological syndrome, in days or weeks. Brain MRI was always normal. Mild cerebrospinal fluid pleocytosis was reported in only two patients. The following syndromes were identified on admission: A medullary syndrome was seen in 11 (50%) patients. Seven of them presented with dysphagia, dysarthria and central hypoventilation. The other four in addition of bulbar symptoms, without central hypoventilation, presented pontine manifestations. Six (27%) patients developed a pontine syndrome with paresis of the VI or VII cranial nerves, nystagmus, usually vertical, and gait ataxia. There was a rapid downward progression to the medulla in all patients. Five (23%) patients presented a ponto-mesencephalic syndrome with uni- or bilateral palsy of the III and VI cranial nerves and gait ataxia, but rapidly progressed to complete gaze paresis and medullary dysfunction. Conclusions: The study confirms the predominant medullary involvement but also shows that half of the patients present with clinical features that indicate an upper, mainly pontine, dysfunction before downward progression.